Herbicidal Combinat ion for Effect ive Management of Complex Weed Flora in Transplanted Rice (Oryza sat iva L.) - Yadav, Vimal Raj; Singh, V. Pratap; Chaturvedi, Sumit; Banga, Akshita; Singh , Samar Pal (International Journal of Bio-resource and Stress Management, 2015)
Long term continuous use of similar herbicide is major culprit for weed shift and herbicide resistance. Therefore, a field experiment was conducted at Norman E. Borlaug Crop Research Centre of G.B. Pant University of Agriculture and Technology, Pantnagar during kharif 2012 to evaluate the performance of new broad spectrum herbicide molecules. Pre-emergence application of Pretilachlor 750 g ha-1 with no irrigation during initial one week along with post-emergence application of Bispyribac-Na 20 g ha-1 provided broad spectrum control of complex weed flora at 30 and 60 days after transplanting (DAT) resulted in significantly lower weed density and dry matter than rest of the weed control treatments. This treatment thus, provided higher weed control efficiency (98.7%) and yield (5729 kg ha-1), than test treatment i.e., pre-emergence application of Pretilachlor alone. However, one conoweeding (15 DAT)+one hand weeding (45 DAT) recorded higher weed density and dry matter at both the stages. Alone post-emergence application of Bispyribac-Na and twice hand weedings produced at par yield with Pretilachlor 750 g ha-1 with no irrigation during initial one week along with application of Bispyribac-Na 20 g ha-1. Among different doses of Penoxsulam, the increase in dose of Penoxsulam caused significant reduction in weed density and dry matter thus registered higher grain yield. Post-emergence application of Penoxsulam at 22.5 and 25 g ha-1 produced comparable yield with Bispyribac-Na. Conoweeding+one hand weeding was found least effective compared to rest of the treatments.